2019
DOI: 10.1177/0040517519845685
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel plasma-based method of introducing maleic acid and pentaerythritol phosphate urea salt onto polyester fabrics for durable flame-retardant treatment

Abstract: In this work, a novel anti-flame poly(ethylene terephthalate) (PET) fabric was successfully fabricated by plasma-based technology combined with pad-dry-cure treatment finishing. Low-temperature plasma can graft maleic acid (MA) onto a PET polymer backbone, which can activate the PET fiber and provide the opportunity of reaction with pentaerythritol phosphate urea salt (PEPAS) to achieve an excellent and durable anti-flame ability. Furthermore, the chemical reaction between PET-MA and PEPAS can form a complex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Fumaric acid (FA, ( E )-HOOC–CHCH–COOH, also known as trans -butenedioic acid) and maleic acid (MA, ( Z )-HOOC–CHCH–COOH, or cis -butenedioic acid) are the simplest dicarboxylic acids bearing a CC bond. Both FA and MA are naturally occurring substances , that receive applications in different areas, e.g., as corrosion inhibitors, feedstock in the production of polyester resins, and antiscaling agents. , They are also used in the food and cosmetics industries and in medicine. , However, the use of maleic acid as a food additive has been banned in both Europe and the USA because of its potential toxicity to the kidneys …”
Section: Introductionmentioning
confidence: 99%
“…Fumaric acid (FA, ( E )-HOOC–CHCH–COOH, also known as trans -butenedioic acid) and maleic acid (MA, ( Z )-HOOC–CHCH–COOH, or cis -butenedioic acid) are the simplest dicarboxylic acids bearing a CC bond. Both FA and MA are naturally occurring substances , that receive applications in different areas, e.g., as corrosion inhibitors, feedstock in the production of polyester resins, and antiscaling agents. , They are also used in the food and cosmetics industries and in medicine. , However, the use of maleic acid as a food additive has been banned in both Europe and the USA because of its potential toxicity to the kidneys …”
Section: Introductionmentioning
confidence: 99%
“…For a durable FR treatment of synthetic fabrics, grafting through radical formation is a very common approach especially for synthetic textiles since they lack of functional groups to derivative as in case of natural fibers. A plasma treatment based method was employed to graft a FR system to PET fabric (Scheme 23) [84]. Alkali deweighting treatment of PET was carried out before the FR treatment to allow the fabric surface to have favorable interaction with the FR compound.…”
Section: Treatments For Synthetic Textilesmentioning
confidence: 99%
“…Majority of new FR compounds published in the literature are from academic institutes. Though these compounds are shown to be effective as FRs, their synthetic strategy is not feasible in industry [84], their treatments lack long-term durability [68] and their preliminary toxicity data are rarely [174] provided. Even though one passes the first hurdle of developing an effective FR compound, the reproducibility of test results obtained in the lab scale and upscaling the chemistry remain.…”
Section: Commercialization Of New Fr Technologiesmentioning
confidence: 99%
“…Silicon nanoparticles [70,71]treated the synthetic fibers protect the polymeric fibers from contact with oxygen gas which then reduces the heat transfer. It was reported that [72] by layering a multilayered thin film of silica onto polyester textiles (PET), the flame retardant properties are improved.…”
Section: Flame Retardant Applicationsmentioning
confidence: 99%